Late payment problems among contractors in Malaysia - Mohd. Nazir, Noor Zarina (2006)
Late payment to contractors is a common cause of disputes in the construction industry all over the world. Although there has been a remarkable progress in Malaysia’s construction industry in the recent years, problems arising from payment issues are getting more serious. The rapid increase of the late payment issues nowadays has gone to the point that it tends to decrease the good image of construction industry in Malaysia. The aims of this study is to investigate the consequence of the late payments problems confronted by contractors in Malaysia and to proposed strategic actions that could be taken by the contractors in securing their payments. The methodology adopted was through literature search and questionnaire surveys. This study was limited to contractors within Malaysia. Frequency and average index analysis was used to analyze the data collected. Results of the survey indicate that the main factors of late payments problems come from the clients-related category. Impact of late payment that has the highest index was the negative relationship it created between developers and contractors. The last section of analysis indicated that most contractors choose to do a follow up using formal procedure in the case of late payment. In conclusion, it is hoped that these findings will guide effort to improve the payments problems of the Malaysia construction industry, and will be useful to draft a better way in seeking right for the contractors in getting payment on the stipulated time.